DERMATITIS KONTAK AKIBAT KERJA PADA PEKERJA GARMEN - Pramantara, I Made Stepanus Biondi; Brathiarta, I Made (E-Jurnal Medika Udayana; vol 3 no 1 (2014):e-jurnal medika udayana)
Occupational contact dermatitis is a dermatitis that occurs due to contact with the materials that exist in the workplace, and this is not the case if the person does not work. In the textile workers, the incidence of occupational contact dermatitis ranks fourth of all occupational skin diseases annually in Finland. Contact dermatitis is of two kinds, namely contact dermatitis ( DKI ) arising through non-immunologic mechanisms and allergic contact dermatitis ( DKA ) as a result of specific immunologic mechanism ( slow type hypersensitivity reaction ( type IV ) ) . To assign a material cause of contact dermatitis required a careful history taking about, a complete medical history, physical examination and patch test and is also required investigation into the workplace to observe the work and what materials are usually in contact with the patient when the patient works. Some of the materials most commonly cause dermatitis due to work in garment workers are resins, formaldehyde and dyes. Handling contact dermatitis can be divided into non-pharmacological therapy and pharmacology. The best way to overcome work-related contact dermatitis is prevention by avoiding contact of the material causes. Long-term prognosis of occupational contact dermatitis is very bad, despite the best efforts of treatment and change the type of work has been done.
Keywords: contact dermatitis, garment, allergic, irritant